Definitive Hematopoiesis in the Yolk Sac Emerges from Wnt-Responsive Hemogenic Endothelium Independently of Circulation and Arterial Identity. (23rd October 2015) - Frame, Jenna M.; Fegan, Katherine H.; Conway, Simon J.; McGrath, Kathleen E.; Palis, James
Abstract: Adult-repopulating hematopoietic stem cells (HSCs) emerge in low numbers in the midgestation mouse embryo from a subset of arterial endothelium, through an endothelial-to-hematopoietic transition. HSC-producing arterial hemogenic endothelium relies on the establishment of embryonic blood flow and arterial identity, and requires β-catenin signaling. Specified prior to and during the formation of these initial HSCs are thousands of yolk sac-derived erythro-myeloid progenitors (EMPs). EMPs ensure embryonic survival prior to the establishment of a permanent hematopoietic system, and provide subsets of long-lived tissue macrophages. While an endothelial origin for these HSC-independent definitive progenitors is also accepted, the spatial location and temporal output of yolk sac hemogenic endothelium over developmental time remain undefined. We performed a spatiotemporal analysis of EMP emergence, and document the morphological steps of the endothelial-to-hematopoietic transition. Emergence of rounded EMPs from polygonal clusters of Kit + cells initiates prior to the establishment of arborized arterial and venous vasculature in the yolk sac. Interestingly, Kit + polygonal clusters are detected in both arterial and venous vessels after remodeling. To determine whether there are similar mechanisms regulating the specification of EMPs with other angiogenic signals regulating adult-repopulating HSCs, we investigated the role of embryonic blood flow and Wnt/β-catenin signaling during EMP emergence. In embryos lacking a functional circulation, rounded Kit + EMPs still fully emerge from unremodeled yolk sac vasculature. In contrast, canonical Wnt signaling appears to be a common mechanism regulating hematopoietic emergence from hemogenic endothelium. These data illustrate the heterogeneity in hematopoietic output and spatiotemporal regulation of primary embryonic hemogenic endothelium. Abstract : Definitive hematopoiesis initiates as a broad temporal wave of yolk sac-derived erythromyeloid progenitor (EMP) colony-forming potential (red arrow with shaded area). EMPs emerge from flattened hemogenic endothelium (HE; green dotted line) between embryonic day (E)8.5 through as late as E10.5-11, which correlates with the known temporal requirement for Runx1 in mediating EMP formation (green trapezoid). EMPs emerge from both arterial and venous regions of the yolk sac and do not require blood flow, but are regulated by Wnt signaling. Endogenous canonical Wnt signaling in the yolk sac is most robust during hematopoietic commitment (blue trapezoid), and increases EMP production from hemogenic endothelium at E8.5.